Spirituality in the Workplace: What Does It Mean? A Literature Review - Temel Eginli, Aysen (Advances in Social Sciences Research Journal, 2017)
The concept of spirituality has become even more critical in the 21st century so that organisations have had a transition from modern paradigm to spiritual paradigm. In organisations, the concepts of spirituality, spiritual workplace, and spirituality in the workplace have become a matter of debate among various disciplines. Although attaching importance to the spirituality or spiritual values in organizations have become remarkable in the 1990s, the discussion on the concept and difficulty in defining the concept persists. Besides, it's positively associated with the concepts of personal spirituality, intrinsic, satisfaction, distress, development, wellbeing. It occurs as the concept of organizational spirituality; spirituality based organizations emerged as the spirituality had been noticed by the organisation and included into the organizational processes so that the positive results have been obtained such as job satisfaction of these organizations, organizational well-being, employee empowerment, and so on. Though, it is explained that the competitive power of organizations is closely related to the inclusion of spirituality organizational culture and climate. This study deals with the concepts and approaches of the spirituality and the spirituality in organizations (workplace spirituality/spiritual workplace) and the benefits of spirituality to organizations.